Teknologi dan Pembelajaran : Memanfaatkan Macromedia Flash dalam Model Learning Cycle 5E untuk Mendukung Pemahaman Konsep Matematis - Muinah, Muinah; Sari, Affrylia; Darwanto, Darwanto; Ningrum, Fhela Vhantoria (Eksponen, 2025)
This study aims to determine the effect of applying the Learning Cycle 5E model assisted by Macromedia Flash media on the understanding of quadrilateral concepts by seventh-grade students at SMP Islam Alfalah Abung Tinggi. This research uses a quasi-experimental design with the Nonequivalent Control Group Design method. The sample consists of two classes, with the experimental class taught using the Learning Cycle 5E model assisted by Macromedia Flash, and the control class taught using traditional learning models with PowerPoint. Data were collected using a validated descriptive test and analyzed using t-test to examine the differences between pretest and posttest scores. The analysis results show a significant effect of the Learning Cycle 5E model assisted by Macromedia Flash on improving students' concept understanding, with a t-value = 2.863 > t-table = 1.671, indicating that the alternative hypothesis is accepted, and the null hypothesis is rejected. This finding contributes to the development of mathematics education, specifically in enhancing the understanding of quadrilateral concepts through more interactive and engaging teaching methods.